Le conseguenze bioetiche dell’emergenza sanitaria e la biopolitica della pandemia (Società e diritti, 2020)
AbstractThe essay briefly addresses the bioethical and biopolitical issues that have arisen following the health emergency due to the Convid-19 epidemic. In particular, the opinion of the CNB on the pandemic emergency isexamined and the debate opened by the biopolitical reflection of the philosopher Giorgio Agamben regarding the limitation of fundamental freedoms and the distribution of health resources is taken into account. Finally, the pandemic is examined as a historical social event that can generate a renewed consideration of the bioethics of care based on the vulnerability of the human being